INNV-21. COMPLETE RESPONSE TO ADJUVANT TEPOTINIB IN A PATIENT WITH NEWLY DIAGNOSED DISSEMINATED GLIOBLASTOMA (GBM) HARBORING MET AMPLIFICATION. (12th November 2021) - Pham, Lily; Gann, Claudia; Schumacher, Karl Maria; Vlassak, Soetkin; Swanson, Todd; Highsmith, Kaitlyn; Ou, Alexander; Clarke, Nathan; Aaroe, Ashley; Robell, Lindsay; O'Brien, Barbara; Nash, Sebnem; et al.
Abstract: MET oncogene encodes a receptor-tyrosine-kinase which drives cell proliferation, invasion and angiogenesis in a number of solid cancers including GBM where the incidence of MET amplification is 2-5%. Tepotinib is a highly selective blood-brain-barrier penetrant oral c-MET inhibitor recently FDA approved for MET-exon-14 altered non-small cell lung cancer (NSCLC). Here, we report complete radiographic response to tepotinib in a patient with newly-diagnosed disseminated GBM harboring MET amplification. A 29-years-old male presented with progressive headache. MRI brain showed a large heterogeneously enhancing intraventricular mass with epicenter in the right lateral ventricular trigone and enhancing nodules in bilateral cerebellum. MRI spine showed multifocal enhancement along the periphery of the cervicothoracic spinal cord and cauda equina concerning for leptomeningeal disease. He underwent right temporal lobectomy and subtotal resection of the mass. His KPS was 90 post-surgery due to dizziness. Pathology was consistent with GBM, IDH wild-type, MGMT-unmethylated and MET amplification at 7q31.2. He completed proton craniospinal irradiation at 3600cGy followed by boost to the tumor bed at 2400cGy without concurrent temozolomide (TMZ) due to the large radiation field. He completed two cycles of adjuvant TMZ which was put on hold due to myelosuppression. He subsequently started tepotinib monotherapy at 1000mg daily obtained on a compassionate IND. MRIs after one month of therapy showed resolution of areas of enhancement in the brain and spine. He had grade 1 creatinine elevation and abdominal discomfort and dose was reduced to 500mg daily after two cycles. Nineteen weeks after initiation of tepotinib, his complete response persists, and he remains clinically stable with mild chronic dizziness. Trials of targeted therapy in molecularly-unselected GBM have been largely disappointing, however, this case demonstrates the promise of targeting MET using tepotinib in GBM. A clinical trial of tepotinib in MET-amplified GBM and NSCLC brain metastasis is currently underway at MD Anderson.